Digital educational content «moscow electronic school» in the students learning and training process - Kolotilshchikova S.V.,; Nizametdinova Z. Kh. ,; Andryushchenko O.N.,; Polyshkene Y. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to justify the introduction of digital tools for learning the content of the «Moscow Electronic School» (MES) in the practice of the educational and training process of students for the accelerated development of new types of sports. Methods and structure of the study. The experiment took place on the basis of the Russian Economic University named after G.V. Plekhanov and Financial University under the Government of the Russian Federation. Two equal groups were created: experimental (N1, n=50) and control (N2, n=50). In group N1, digital learning tools «Libraries of electronic materials» of digital educational content «Moscow Electronic School» (MESH) have been implemented: video files, images, audio files, arranged in thematic blocks by sections of training, levels of training. In group N 2, traditional learning technologies were used. Results and conclusions. The use of the educational content «Moscow Electronic School» (MES) in the practice of the educational and training process in the elective discipline Physical culture and sport in the university increases the effectiveness of the educational process due to the use of digital learning tools and information computer technologies in the real conditions of the educational and training class and in a remote format; for the teacher – a selection of electronic scenarios of the educational and training session in accordance with the preparation section, the level of preparedness of the participant at the current moment; for a student who has started to master a new kind of sport - to quickly and correctly form an idea about a new element of technique and implement it in motor activity with a minimum number of errors; raise the level of physical and functional preparedness independently.